Modelo de negocio para el desarrollo de energía urbana sostenible para Guayaquil - Pine Tobar , William; Alfonso Robaina, Daniel (Ingeniería Industrial, 2025)
The urban areas with the highest urban and population growth, such as the city of Guayaquil, are the main consumers of energy and therefore require greater consumption of fossil fuels for electricity generation. In some countries, large-scale progress is being made in the energy transition from fossil fuels to sustainable energy sources; however, the construction of new infrastructure is necessary. Given this scenario, electricity generation through renewable energy sources is the most viable option for the energy sustainability of cities, even being the best alternative until local governments invest in the construction of the necessary infrastructure. By means of the bibliometric analysis of journals with greater influence in the SCImago indicator, a business model for the development of sustainable urban energies in the city of Guayaquil is proposed; reaching the conclusion that the proposed business model is oriented to a premium service with aggregates in the final product.